Dampak Bagi Ketenagakerjaan Terkait Adanya RUU Kia (Kesejahteraan Ibu Dan Anak) - Elza Qorina Pangestika (Departement of Mathematics Education, 2024)
The preparation of the Draft Law on the Welfare of Mothers and Children (RUU KIA) is the Government's commitment to realizing a stunting-free golden generation. The MCH Bill provides regulations regarding maternity leave which previously in the Employment Law was 3 months, now it is 6 months. If a mother experiences a miscarriage, leave is given for 1.5 months. The KIA Bill also provides regulations regarding leave for husbands who accompany their wives giving birth, which was originally 2 days in the Manpower Law, now it is 40 days. If the wife experiences a miscarriage, the leave given is 7 days. To realize the objectives of the KIA Bill, providing these leaves is very good. However, this is certainly a matter of debate if it is related to employment. If workers are on leave for too long, it will certainly affect the amount of production, not to mention if there is an inability of employers to continue to provide wages to workers who are on leave. After this research was carried out, we now know the impact on employment related to the KIA (Mother and Child Welfare) Bill. The research method used is a qualitative method with data collection techniques using observation and in-depth interviews. Qualitative data analysis techniques with stages of data reduction, data presentation and drawing conclusions. The output of this research will be an accredited national journal. It is hoped that the benefits of this research can provide input for the government, employers and workers in responding to the policies contained in the MCH (Mother and Child Welfare) Bill if the MCH Bill is officially passed as law. The output of this research is news articles published in national journals.